2022
DOI: 10.1007/s10344-022-01588-5
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian otter Lutra lutra diet mirrors the decline of native fish assemblages in a semi-arid catchment (River Segura, SE Spain)

Abstract: In semi-arid environments, the effects of irregularly distributed rainfall, flow regulation and water inter-basin transfer enhance the spread of non-native fish to the detriment of native communities. In the River Segura, since the 1980s the number of non-native fish species has progressively increased, also because of the building of water transfer facility connecting the rivers Segura and Tajo. With the aim of highlighting how man-driven changes in the diversity of fish communities affect the diet of top-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…It has been shown that the otter diet is more diverse in less stable environment, where non-sh prey are more often preyed upon (Ruiz-Olmo and Jimenez 2009; Dettori et al 2022). In our study, as in many other European habitats, alternative vertebrate prey other than amphibians, played a little role.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the otter diet is more diverse in less stable environment, where non-sh prey are more often preyed upon (Ruiz-Olmo and Jimenez 2009; Dettori et al 2022). In our study, as in many other European habitats, alternative vertebrate prey other than amphibians, played a little role.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being strictly linked to aquatic habitats, otters may also benefit from well-preserved riparian forests, which may offer suitable resting sites especially in human-disturbed areas (Weinberger et al, 2019). Lack of riparian forest (Karr and Schlosser, 1978;Jones et al, 1999;Gregory et al, 1991), as so as water pollution (Changeux and Pont, 1995;Vila-Gispert et al, 2002), may also alter the abundance and distribution of fish, otters' main food resource (Dettori et al, 2022), affecting the use by otters of deforested stretches.…”
Section: Discussionmentioning
confidence: 99%